In situ isotopic studies of the U-depleted Allende CAI Curious Marie: Pre-accretionary alteration and the co-existence of 26Al and 36Cl in the early solar nebula. (15th June 2017) - Tang, Haolan; Liu, Ming-Chang; McKeegan, Kevin D.; Tissot, Francois L.H.; Dauphas, Nicolas
Abstract: The isotopic composition of oxygen as well as 26 Al- 26 Mg and 36 Cl- 36 S systematics were studied in Curious Marie, an aqueously altered Allende CAI characterized by a Group II REE pattern and a large 235 U excess produced by the decay of short-lived 247 Cm. Oxygen isotopic compositions in the secondary minerals of Curious Marie follow a mass-dependent fractionation line with a relatively homogenous depletion in 16 O (Δ 17 O of −8‰) compared to unaltered minerals of CAI components. Both Mg and S show large excesses of radiogenic isotopes ( 26 Mg ∗ and 36 S ∗ ) that are uniformly distributed within the CAI, independent of parent/daughter ratio. A model initial 26 Al/ 27 Al ratio [(6.2 ± 0.9) × 10 −5 ], calculated using the bulk Al/Mg ratio and the uniform δ 26 Mg ∗  ∼ +43‰, is similar to the canonical initial solar system value within error. The exceptionally high bulk Al/Mg ratio of this CAI (∼95) compared to other inclusions is presumably due to Mg mobilization by fluids. Therefore, the model initial 26 Al/ 27 Al ratio of this CAI implies not only the early condensation of the CAI precursor but also that aqueous alteration occurred early, when 26 Al was still at or near the canonical value. This alteration event is most likely responsible for the U depletion in Curious Marie and occurred at most 50 kyr after CAI formation, leading to a revised estimate of the early solar system 247 Cm/ 235 U ratio of (5.6 ± 0.3) × 10 −5 . The Mg isotopic composition in Curious Marie was subsequently homogenized by closed-system thermal processing without contamination by chondritic Mg. The large, homogeneous 36 S excesses (Δ 36 S ∗  ∼ +97‰) detected in the secondary phases of Curious Marie are attributed to 36 Cl decay ( t 1/2  = 0.3 Myr) that was introduced by Cl-rich fluids during the aqueous alteration event that led to sodalite formation. A model 36 Cl/ 35 Cl ratio of (2.3 ± 0.6) × 10 −5 is calculated at the time of aqueous alteration, translating into an initial 36 Cl/ 35 Cl ratio of ∼1.7–3 × 10 −5 at solar system birth. The Mg and S radiogenic excesses suggest that 26 Al and 36 Cl co-existed in the early solar nebula, raising the possibility that, in addition to an irradiation origin, 36 Cl could have also been derived from a stellar source.